Bullying behavior and its implications for the formation of student character - Rezky, Andi Muh; Mukramin, Sam'un; Ashar, Ashar (Program Pascasarjana Universitas Negeri Yogyakarta, 2025)
Bullying is not a new phenomenon, yet its prevention and management must be pursued in a continuous, collaborative, and systematic manner, particularly through character education, active teacher involvement, and support from families and communities. This study aims to explore the forms of bullying behavior and their implications for character development among students at UPT SPF SD Negeri Sangir, Makassar. Using a qualitative descriptive approach in the form of a case study, data were collected through observation, in-depth interviews, and documentation involving 12 informants, including students, teachers, and parents. The results show that bullying occurs in almost all grade levels, predominantly in the forms of verbal and physical abuse. The impacts of bullying are highly significant on student character, affecting victims—who tend to become passive, anxious, and lack self-confidence—as well as perpetrators—who display aggressive behavior and a lack of empathy. The development of positive character traits such as empathy, responsibility, and respect are hindered by an unsupportive environment. This study highlights the crucial role of teachers, parents, and the school environment in preventive, curative, preservative, and referral (reveral) efforts to address bullying. Systematic and continuous character education is key to creating a safe learning climate that supports students’ holistic personality development.